Optimization of microprobe analysis of cementitious materials incorporating glass powder under electron beam to avoid alkali migration - Wena de Nazaré do Rosário Martel; Josée Duchesne; Benoît Fournier (Cement)
The growing use of alkali-rich glass powder (GP) as a supplementary cementitious material (SCM) in concrete has led to a rising number of studies focused on the microstructure of cementitious matrices incorporating GP. Electron probe microanalyzer (EPMA) is commonly used to characterize cementitious materials. However, alkali migration induced by electron irradiation - a well-known phenomenon in inorganic materials - remains underexplored in this context. This migration often leads to underestimation of Na and K and overestimation of Si and Ca, thus compromising the analysis of key elements in cementitious hydrates, such as C-S-H. Due to the lack of a tailored protocol for EPMA analysis of alkali-rich SCMs, this study established analytical conditions to minimize errors in quantifying pozzolanic GP. Mixed glass culets and GP particles embedded in 7-year-old ternary concrete made with GP and silica fume were analyzed using ten different current densities by varying beam size, current, and the sub-counting method. The results show that alkali migration is highly sensitive to material composition and irradiation conditions. Na losses exceeded 70% as Ca and Si overestimation reached approximately 13% at current densities above 0.354 nA/μm². Literature-reported densities often surpass this threshold. At those conditions, the implementation of a sub-counting method effectively reduces the Na loss to 3%. However, it introduced a tendency for Na overestimation at lower current densities. Among all conditions, a beam diameter of 6 µm and a current of 10 nA, was the most accurate, reducing losses to under 2% and closely matching the reference glass analysis.